Comprehensive evolution and molecular characteristics of a large number of SARS-CoV-2 genomes reveal its epidemic trends. (November 2020) - Bai, Yunmeng; Jiang, Dawei; Lon, Jerome R; Chen, Xiaoshi; Hu, Meiling; Lin, Shudai; Chen, Zixi; Wang, Xiaoning; Meng, Yuhuan; Du, Hongli
Highlights: Outgroup was not used due to the unknown source of SARS-CoV-2. 16, 373 SARS-CoV-2 genomes were included in this evolution analysis. Nine key specific sites of high linkage and four major haplotypes were found. Epidemic trends and possible earlier origins of SARS-CoV-2 were indicated. Abstract: Objectives: To further reveal the phylogenetic evolution and molecular characteristics of the whole genome of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) based on a large number of genomes and provide a basis for the prevention and treatment of SARS-CoV-2. Methods: Various evolution analysis methods were employed. Results: The estimated ratio of the rates of non-synonymous to synonymous changes (Ka/Ks) of SARS-CoV-2 was 1.008 or 1.094 based on 622 or 3624 SARS-CoV-2 genomes and nine key specific sites of high linkage, and four major haplotypes were found: H1, H2, H3 and H4. The results of Ka/Ks, detected population size and development trends of each major haplotype showed that H3 and H4 subgroups were going through a purify evolution and almost disappeared after detection, indicating that they might have existed for a long time. The H1 and H2 subgroups were going through a near neutral or neutral evolution and globally increased with time, and the frequency of H1 was generally high in Europe and correlated with the death rate ( r >0.37), suggesting that these two haplotypes might relate to the infectivity or pathogenicity of SARS-CoV-2. Conclusions: Several key specific sites and haplotypes related to the infectivity or pathogenicity of SARS-CoV-2, and the possible earlier origin time and place of SARS-CoV-2 were indicated based on the evolution and epidemiology of 16, 373 SARS-CoV-2 genomes.